Distribution Optimization and Its Impact on Manpower Planning in the Tilapia Fillet Processing Industry - Antrika Yuniarti; Hendarsjah, Hidajat (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines distribution optimization and its impact on manpower planning in the tilapia fillet processing industry in East Java, Indonesia. The research aims to evaluate how optimized distribution configurations influence workforce requirements across supply chain nodes. A quantitative analytical approach was applied using operational distribution data, with distribution optimization conducted through linear programming and the relationship between distribution volume and workforce demand analyzed using Spearman correlation. The results indicate that optimized distribution structures significantly reduce transportation costs and improve workforce allocation efficiency. The findings highlight that distribution optimization can support more adaptive manpower planning and enhance operational efficiency in fisheries supply chains.